Tensions in impressions: Dialectical nature of impression management in GoodGovPH - De Quiroz, Azhley Katherine M. (Animo Repository, 2023)
As communication technologies continue to increase, the landscape for impression management has expanded beyond physical interactions to encompass diverse mediated platforms with unique affordances. This study examines the interplay of media affordances, impression management, and dialectical tensions in relationships between directors and their members. Based on 19 semi-structured interviews with GoodGovPH, this study identifies and explores four sets of impression management tactics: (1) dodging response versus exerting social pressure, (2) multifunctioning versus hogging individual growth, (3) encouraging personal endeavors versus neglecting duties, (4) monopolizing versus bypassing. Analysis reveals that the actions of directors and members were often in dialectical tension, playing out through multiple media in a tactic–countertactic dynamic that played an essential role in shaping supervisor–subordinate relationships. Building on research on impression management processes online and in organizations, I extend this research to explain impression management practices among directors and members involved in non-profit, volunteer organizational work in the Philippines who rely on various communication media to push forward their advocacies through community initiatives and programs.